Traffic and Technological Assumptions for the Metro in the City of Split - Višnjić, Vinko; Pušić, Marko; Žižić, Ivan (Promet - Traffic&Transportation, 2007)
Rationalization of the traffic systems in major cities, whichincludes Split, is possible at present only by providing a more diverseand higher quality supply of public urban transport.In Split the situation in public urban transport shows that itdoes not meet its basic function. Only partial or transitional solutionsare offered. All this contributes to the delay in makingthe decision which is the only possible one in the city of Split regardingits size and the level of motorization.The solution of the public urban transport lies in the introductionof the metro system through phase construction. Eachphase represents in fact the construction of one line. Due to thecomplexity of the construction of the underground section (tunnelconstntction in the centre of the City) the first phase is themost demanding one regarding construction works, with twometro lines intersecting (the need to build two-level stations)and therefore this section is the most complex and the most expensivepart in the network of the metro line system.